Fluctuation of BCR-ABL1 qPCRIS level beyond 0.1%IS after stopping tyrosine kinase inhibitor in chronic myeloid leukaemia patients with deep molecular response for at least two years - Kuan, Jew-Win; Chang, Kian-Meng; Chin, Lee Phan; Wong, Shu Ping; Lim, Soo Min; Toh, See Guan; Loh, Weng Khean (NCBI Literature Resources, 2021)
Fluctuation of BCR-ABL1 real-time quantitative polymerase chain reaction in International Scale (qPCRIS ) level below major molecular response (MMR) (0.1%IS ) is a known phenomenon after stopping tyrosine kinase inhibitor (TKI) in chronic myeloid leukaemia (CML) patients who are attempting treatment free remission (TFR). We report here four cases of fluctuation beyond MMR during conduct of a Malaysia Stop TKI Trial (MSIT) to examine the validity of the commonly used relapse criterion – loss of MMR for one reading – aiming to provide evidence in setting relapse criteria for future CML patients who want to attempt TFR.